Performance and carbon deposition over Pd nanoparticle catalyst promoted Ni/GDC anode of SOFCs in methane, methanol and ethanol fuels - Babaei, Alireza (2013)
The electrochemical performance and carbon deposition on palladium catalyst promoted Ni/Gd0.1C0.9O1.95 (Ni/GDC) anode in methane and alcohol fuels like methanol and ethanol are investigated at open circuit potential and under dc bias using electrochemical impedance spectroscopy technique. Presence of Pd nanoparticle catalyst significantly promotes the electrocatalytic activity of Ni/GDC for the electrooxidation reaction in methane and in particularly in methanol and ethanol fuels. For instance, in the case of methanol oxidation reaction, there is clear separation of the impedance arcs at high and low frequencies and activation energy for the reaction is reduced by ∼33% on a 0.15 mg cm−2 PdO impregnated or infiltrated Ni/GDC anode. The transitional impedance response study when the inlet gas is switched from hydrogen to methane or alcohol fuels indicates that the oxidation reaction in methane and alcohol fuels is most likely dominated by adsorption, dissociation and diffusion steps of the reaction. Carbon deposition is also observed on Pd-infiltrated Ni/GDC in methanol and ethanol, but different from that observed in methane, there is no filament carbon fibers formation on the Pd-impregnated Ni/GDC surface in methanol fuel.